What drives online impulse buying among Zoomers on TikTok in an emerging market? A new model based on flow theory - Obadă, Daniel-Rareș; Țugulea, Oana (Frontiers in Communication, 2024)
Our article aims to investigate the factors, precisely motives for TikTok use, perceived ad intrusiveness, attitude toward advertising, ad credibility, ad value, and online flow experience, driving buying impulsiveness among Generation Z users on TikTok. The results indicate that motives for TikTok use negatively affect perceived ad intrusiveness while positively affecting the online flow experience and ad credibility. Attitude towards advertising negatively impacts perceived ad intrusiveness, while attitude towards advertising positively influences ad credibility and value. Furthermore, ad credibility has a positive impact on ad value, which, in turn, positively influences online impulse buying. As such, adapted ad content leads to a positive attitude toward advertising, creating an optimal experience on the platform and a positive perception of ads regarding credibility and value.